Poor Glycemic Control Correlates with Iron Deficiency Anemia in Type 2 Diabetes Mellitus - Kaltsum, Talitha Imani; Pusparini, Pusparini (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Glycated hemoglobin (HbA1c) has been used extensively to diagnose and monitor diabetes mellitus (DM). Patients with type 2 DM are at risk of experiencing comorbidities and complications such as iron deficiency anemia (IDA). This study aimed to determine the correlation of HbA1c with iron deficiency anemia (IDA) in type 2 DM.Methods: This cross-sectional study was conducted on 115 types 2 DM patients at a hospital in South Jakarta, Indonesia from November to December 2021. Data on HbA1c levels and IDA were obtained from medical records. Data were analysed with the Chi-Square test and significancy at p<0.05.Results: In total, 43 men and 72 women with type 2 DM were included, with predominantly age over 45 years (89.6%), had DM for more than ten years (55.7%), had obesity I (53.9%), and with hypertension as the most common comorbidity (65.2%). Furthermore, the patients did not smoke (64.3%), had poor glycemic control ((76.5%) and had anemia (58.3%). There was a significant relationship between HbA1c levels and IDA (p = 0.003).Conclusions: This study shows a relationship between HbA1c and IDA in type 2 DM, therefore, DM patients with poor glycemic control need to be well monitored for iron deficiency anemia.